Association of the MC4R gene with growth traits and meat quality in Colombian hair sheep (Journal of Advanced Veterinary and Animal Research, 2023)
Objective: The objective of this study was to associate the 1016G > A variant of the melanocortin-4 receptor gene with lamb’s weight, growth, and meat quality in the Colombian hair sheep breed. Materials and Methods: A total of 168 lambs, weights were measured at birth weight (BW), at weaning adjusted weaning weight (AWW), at 6 months [adjusted weight (AW180)], at slaughter adjusted slaughter weight (ASW), daily weight gain preweaning daily gain (preWDG), and postweaning daily gain (postWDG) weaning, and after slaughter, pH, texture, and cook-loss (CL) in the longissimus thoracis et lumborum (LTL) muscle according to the American Meat Science Association methodology. The 1016G > A genotypes were obtained by sequencing. Genotypic and allele frequencies, heterozygosities, and Hardy–Weinberg equilibrium (HWE) were estimated. Using a generalized linear model, the genotype and the allelic substitution effect were associated with the evaluated traits. Results: The heterozygous genotype (0.48) and G allele (0.61) were the most frequent. Heterozygosities were similar (0.47), indicating HWE. The genotype affected the BW (p < 0.05), with a higher value for the GG genotype (2.69 kg). AWW (12.75 kg), AW180 (19.67 kg), and ASW (31.21 kg) weights and daily weight gain (preWDG = 115.41 gm; postWDG = 96.16 gm) were not associated. Average pH, Warner-Bratzler shear force, and CL were 5.75 units, 49.46 N, and 32.02%, with no genotype effect. The G > A substitution only affected BW at −388 gm (p < 0.05). Conclusion: The 1016G > A variant is polymorphic and affects the BW but no other growth traits or the meat quality of the LTL muscle.  J. Adv. Vet. Anim. Res., 10(3): 449–457, September 2023http://doi.org/10.5455/javar.2023.j698